2005
DOI: 10.1086/429876
|View full text |Cite
|
Sign up to set email alerts
|

Eleven New γ Doradus Stars

Abstract: We present new high-dispersion spectroscopic and precise photometric observations to identify 11 new Doradus variables. Seven of these new Doradus stars appear to be single, three are primaries of single-lined binaries, and one has two distant visual companions; none are double-lined or close visual binaries. Several of the stars show spectroscopic line-profile and low-amplitude radial velocity variability indicative of pulsation. All 11 stars are photometrically variable with amplitudes between 8 and 93 mmag … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
72
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 50 publications
(78 reference statements)
5
72
1
Order By: Relevance
“…The resulting combined, normalized spectrum has a S/N of 590 calculated from 5820 to 5821 Å and was used to determine the fundamental parameters and abundances for 43 Cygni. With our spectroscopic data, we also can verify previous reports (e.g., Henry et al 2005;Gerbaldi et al 2007) that 43 Cyg is a single star.…”
Section: Hermes Spectrasupporting
confidence: 88%
See 2 more Smart Citations
“…The resulting combined, normalized spectrum has a S/N of 590 calculated from 5820 to 5821 Å and was used to determine the fundamental parameters and abundances for 43 Cygni. With our spectroscopic data, we also can verify previous reports (e.g., Henry et al 2005;Gerbaldi et al 2007) that 43 Cyg is a single star.…”
Section: Hermes Spectrasupporting
confidence: 88%
“…Using 230 spectra obtained over two years, Jankov et al (2006) studied the line profile variations, detected an additional frequency and attempted a first spectroscopic mode identification. The authors reported a frequency at 1.61 d −1 to be an = 5(±1) and m = 4(±1) and the frequency at 1.25 d −1 -which is f 1 of Henry et al (2005) -to be an = 4(±1) and m = 3(±1) mode. Cuypers et al (2009) confirmed the presence of the previously identified pulsation frequencies using photometric time series in the Geneva system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few stars from other lists (Henry and Fekel 2002;Koen and Eyer 2002) were added as well. In the mean time, the γ Dor character of most of our targets (apart from a few δ Scuti stars) has been confirmed, and they are already listed as bona fide γ Dor stars by Henry et al (2005). Hence, the main goal of our observations is to obtain well defined light curve parameters (frequencies, amplitudes, phases) in the 7 colours of the Geneva photometric system for all the observed variable stars.…”
Section: Introductionmentioning
confidence: 74%
“…In Part I (De Cat et al these proceedings) the analysis of the observations of the variable B stars is discussed. In Part II (this article) the analysis of variable A and F stars is presented, with emphasis on the pulsating γ Doradus stars, hereafter γ Dor stars (see Henry et al (2005) for a class description and a recent list).…”
Section: Introductionmentioning
confidence: 99%